2001
DOI: 10.1021/la010375d
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structure/Property Relationship in Single-Chain Arginine Surfactants

Abstract: In this paper, a systematic investigation into the structure-property relationship of long-chain N-alkyl amide 1, O-alkyl ester arginine 2, and N-acyl arginine methyl ester analogues 3 is reported. The surface properties were studied by adsorption isotherm curves. Biological properties such as antimicrobial activity, hemolysis, ocular irritation, aquatic toxicity, and biodegradability are discussed and correlated with some specific parameters of the surfactants. These surfactants constitute a novel class of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 17 publications
(35 reference statements)
8
86
0
Order By: Relevance
“…Regarding these surfactants, a systematic study on their antimicrobial properties with different tail length was previously reported. 5 This study showed that the efficiency of singlechain surfactants is affected by their alkyl chain length, with a maximum effect for the 12 carbon tail surfactants. Over the past decade, developments on enzyme technology in non-conventional media have opened new possibilities for the synthesis of surfactants from natural sources.…”
Section: Introductionmentioning
confidence: 78%
“…Regarding these surfactants, a systematic study on their antimicrobial properties with different tail length was previously reported. 5 This study showed that the efficiency of singlechain surfactants is affected by their alkyl chain length, with a maximum effect for the 12 carbon tail surfactants. Over the past decade, developments on enzyme technology in non-conventional media have opened new possibilities for the synthesis of surfactants from natural sources.…”
Section: Introductionmentioning
confidence: 78%
“…1); its synthesis and physiochemical properties can be found in the literature [21,23,24]. Double stranded DNA (dsDNA) type XIV from herring testes and T2 DNA were purchased from Sigma and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that it, in analogy with several other mixed cationic-anionic surfactant systems, presents a spontaneous formation of vesicles having a long-term stability; in fact they remain over our extended times of investigation suggesting that they may be thermodynamically stable. Our approach of using an amino acid-based single-tailed surfactant in the catanionic vesicle composition was based on the fact that ALA alone and the mixture of ALA and SOS presented cell viability percentages above 90% (results to be published); ALA has also been reported as being biodegradable [21].…”
Section: Dna Addition To the Vesicle Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding arginine-N-lauroyl amide dihydrochloride (ALA) and N R -lauroyl-arginine-methyl ester hydrochloride (LAM), their synthesis and physicochemical properties can be found in the literature. 38,41,42 ALA and HS have two charges in the headgroup, positive and negative, respectively. All concentrations are presented per charge.…”
Section: Methodsmentioning
confidence: 99%